Reproductive biology and phylogenetic relationships of Vitreorana baliomma (Anura: Centrolenidae) - Zucchetti, Victor Moraes (2020)
Behavioral and population ecology information are lacking for all Vitreorana species inhabiting the Atlantic Forest. Glassfrogs exhibit a diversity of interesting reproductive behaviors, and knowledge of behavioral aspects can help elucidate the complex relationships between clades. In this study, we report on the reproductive behaviors of V. baliomma, a small species of Centrolenidae known only by morphological features of collection specimens. We also describe microhabitat use, advertisement call and the influence of environment on activity of adults and on clutches thickness. Moreover, we conducted phylogenetic analyses using molecular data to assess V. baliomma position in Centrolenidae and confirm their presence within the genus Vitreorana. We sampled two streams in southern state of Bahia, Brazil, between November 2018 and April 2019. For the first time, we confirm the presence of female-only egg-brooding in this species. Oviposition site reflected some of the adult microhabitats. However, clutches were found at lower height and horizontal distances, on both surfaces of the leaves and on larger leaves than those used by adults. Calls of V. baliomma males have one or two notes, and parameter values are similar to other Vitreorana species. Call and phylogenetic analyses validated V. baliomma and confirmed the phylogenetic position within the genus, but the relations in Vitreorana are still nebulous. The number of calling males was positively correlated with air humidity, which probably shows an effect of daily rainfall on reproductive behavior of this species. Our study expands the knowledge on the reproductive biology and elucidate the reproductive behaviors, describing the occurrence of maternal egg-brooding for the species. Our results suggest that egg-brooding is a widespread behavior in Vitreorana. Moreover, this find reinforces the pattern of care evolution in Centrolenidae.